Supuestos teóricos de la enseñanza de las ciencias sociales - de Juan López, Sabino (Educación y Futuro: Revista de Investigación Aplicada y Experiencias Educativas, 2001)
The author first offers a conceptual perspective of the different notions 0f Social Sciences and their place in the current Spanish Educational System; Then he wonders about the justification of his aims, contents and methodology. Do they possess their own knowledge or do they borrow it from other disciplines or outer sciences? What are the different consequences in case one makes neither of these choices?